Analisis Kesabaran dan Penyesuaian Diri Guru dalam Proses Pembelajaran Pada Anak Tunanetra - Marito, Yeni; Azzahrah , Naeza; Nasution, Mutiara Tsaqila Shainy; Aprisya, Safa; Wandiana, Marhama Raisya; Rajagukguk, Wiweka; Boangmanalu, Desi Sri (FKIP Universitas Islam Jember, 2025)
This research aims to investigate the challenges faced by teachers in educating blind students at SLB-A Karya Murni Medan. The approach used in this research is a qualitative case study approach, the data collection method in this research uses interviews and documentation methods. The data obtained was then analyzed using descriptive qualitative with data reduction, data presentation, and conclusion drawing. The number of subjects of this research is 1 teacher of SLB-A Karya Murni. Based on the research that has been conducted, the researcher found problems experienced by SLB-A Karya Murni Medan teachers, namely problems in the learning process. Teachers experience challenges in self-adjustment and patience. The researcher also proposed several solutions and strategies to minimize the challenges faced by SLB-A Karya Murni Medan teachers such as student needs-based training, mentorship by senior teachers, collaboration with psychologists and therapists, emotional and stress management training, application of empathy approach, and psychologist support system. Teachers' self-adjustment and patience levels require not only time and dedication, but also a strong commitment to continuously learn and develop in understanding the unique needs of each student.